Implementasi Nilai Tarian Likurai sebagai Bahan Bimbingan Belajar Siswa Kelas V SDK St. Theresia Atambua - Julmira De Jesus; Silvester P. Taneo; Margaret Djokaho (ARZUSIN, 2025)
This study is motivated by the limited research on students’ lack of interest in and knowledge of local cultural values, particularly ancestral cultural heritage, which contributes to the declining preservation of traditional customs in community life. The objective of this research is to identify the values embedded in the likurai dance that can be implemented in students' daily lives. A qualitative method was employed, with research subjects consisting of one local content teacher, five fifth-grade students, and one community figure, all selected purposively based on their knowledge of and involvement in local culture. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings reveal that the likurai dance contains significant values that can serve as a foundation for character education, including: (1) aesthetic values reflected in movement, costume, and rhythm, which teach students to present themselves neatly and respectfully; (2) ethical values that foster mutual respect and gotong royong (communal cooperation); (3) cultural values that instill appreciation for local heritage; (4) fraternal values that strengthen cooperation and empathy; (5) religious values that promote gratitude; and (6) social values that encourage awareness of interpersonal interaction and mutual support. The study concludes that the values within the likurai dance can be implemented as part of learning guidance, particularly for strengthening students’ character education. The implications of these findings include theoretical contributions in enriching literature on the integration of local cultural values in education, and practical recommendations for the Belu Regency government and primary schools to develop culture-based education from an early age. This study also opens avenues for further research on unexplored cultural values within the likurai dance.